Glycyrrhetic Acid Derivative TY501 Protects Against Lithocholic Acid–Induced Cholestasis - Zheng, Xuemin; Zhu, Shichao; Zhou, Zhixing; Liu, Wei; Xu, Weiren (Drug Research, 2018)
The aim of the study is to investigate the protective effects of TY501 against LCA-induced cholestasis in mice and to explore the potential mechanisms. It was demonstrated that TY501(5, 15 or 45 mg/kg, i.g.) can markedly reduced the level of ALT, AST and ALP which increased by LCA treatment. Meanwhile, TY501 also lowered total bile acids, total bilirubin and total cholesterol levels in serum. Furthermore, TY501 can protect HepG2 cell cultures from LCA-induced cytotoxicity. RT-PCR and Western Blot analysis showed that TY501 recovered the expression of BSEP, MRP2 and NTCP which were down-regulated by LCA. Moreover, mRNA and protein of FXR was also observed in TY501 treated mice significantly accumulation in nucleus. Taken together, It can be concluded that TY501 exerted beneficial effects on LCA-induced cholestasis, possibly via activation of FXR mediated upregulation of BSEP, MRP2 and NTCP.
Keywords: Glycyrrhetic acid derivative; bile acid; FXR; BSEP; MRP2; NTCP